Синтез адаптивної системи управління нестаціонарними технологічними об’єктами харчових виробництв - Заєць, Н. А. (Energy and Automation, 2017)
SYNTHESIS ADAPTIVE CONTROL SYSTEM OF NON-STATIONARY TECHNOLOGICAL OBJECTS FOOD PRODUCTION N. A. Zaiets Most of the processes of chemical and food industry management is multi dimensional objects with complex relationships between variables that are characterized by transience dynamic characteristics. This leads to a deterioration of the quality management systems standard because it depends on the dynamics of the object changes with time. There is a need to build controls, settings are changed (adapted) so that when changing object parameters accuracy and quality of the system remained unchanged. Significant influence on the dynamics of facility management can exercise its nonlinearity mathematical model. Notethenonlinearitythatdictatedexactlydescribegrowthprocessesinthefacilitymanagement, whichinturncausedexcessivedemandsontheaccuracyofthecontrolsystem. Gototheappropriateobjectofnonlinearmodelsinhighmobilitysystem, whentheaveragetimeofregimechangecanbecomparedovertimetransients. Theactionofallthesefactorsleadstotheneedforadaptivemanagement. Themainfeatureofadaptivesystemsisthepresenceofthesepathsbywhichobtainedadditionalinformationabouttheconditionofthesystem, whichisusedtochangeitspropertiesintherightdirectiontoachievetherequiredperformanceandoptimalmanagement. Continuityofoptimalcontrolcanbeachievedbysynthesisofadaptivesystemswith a referencemodel, whichdescribesthedesiredoutputtargetmanagementsystemfor a giveninputaction. Butthedrawbackofthissystemisthecomplexityofthewithdrawalofthereferencemathematicalmodelthataccuratelyandcompletelyadequatelymeetstheobject. Therefore, inthecasewhentheunknownmathematicalmodelusedadaptivesystem ID inwhichthesynthesisofadaptingcircuitbyusing a specialdevice - identifier. Duringtheoperationofthefacilitymayberevisedasthestructureofthemathematicalmodelanditsparameters, iethemodelitselfisadaptiveandidentificationprocessonlinefeedback. Thestudyisstructuringautomatedcontrolsystemusingadaptivesystem ID. TheobjectoftheresearchconsiderdiffusionplantsugarfactoryequippedColumndiffusiondevice, characterizedbynon-stationary, unfavorablepropertiesasfacilitymanagementandisdecisivetechnologicalapparatusofwhichdependsontheefficiencyofthecomplexas a whole. Thecontinuousdiffusioncurrentstationconsistsof: - Columndiffusionapparatus; - Oshparyuvachabeetchips; - Heatersforjuiceandwatersupply. Maintaintherequiredtemperatureinthediffusionapparatusisdecisiveindicatorofthequalityoftheextraction. Intermsofbasicautomationadjustablevariablesaretopofthecolumntemperatureandtemperatureshparyuvachi, keepingthemat a givenlevelisbyregulatingsteamflowtotheheaterjuiceandwatersupply. DevelopmentofAdaptiveautomatedcontrol ID includesthefollowingsteps: 1. Determiningthestructureof a mathematicalmodeloftheobject. 2. Calculationofthemathematicalmodeloftheobject. 3. SelectionAlgorithmregulationthatwillprovidethenecessaryqualityofthesystem. 4.Selectionalgorithmofoptimalcontrollersettingsbasedmathematicalmodeloftheobject. 5.DevelopstructuresAdaptiveautomatedcontrolstationdiffusionanditsimplementation. Todeterminethestructureof a mathematicalmodeloftheobjectwasconstructedandanalyzedparametricdiagramofthemajorthermaldiffusionprocessesintheplant. Houseidentifiedthreetanks: oshparyuvachacapacity, thecapacityofthebottomofthecolumn, thecapacityofthetopofthecolumn. Becausestructureparametersandmathematicalmodelgreatlydependsonthecoefficientofheattransfer, volumeworkenvironment, heat, modeofobjectchangein a widerange, thereistheproblemofdeterminingtheidentificationoftheperiodforwhichthedefinedmathematicalmodeladequatelydescribesabout ’ object. Theexperimentaldatadeterminedthattheperiodofcalculationofthemathematicalmodelis 25 minutes. Tomaintain a giventemperatureoftheobjectappropriateuseofstandardlinearregulationlaw, includingproportional-integralalgorithm. Andintheadaptiveautomaticcontrolunitcalculatestheidentificationofoptimalcoefficientstransmissionsettingsregulators, leaving a constantintegrationtime. Thealgorithmcalculatingtheoptimalsettingscontrolscanbeselectedfrom a numberofsearchmethods, includinggradient, nogradient, randomsearch. Atthesametimeasthesearchcriteriausedintegralquadraticcriterionspecifiedamountofvariationandtheactualvalues ofcontrolledvariablesthroughouttheperiodofadjustment. Theinputdataforthedeviceadaptationareimportantvectorsofcoordinatesstateofficesdisturbances, aswellasdataonthestructureofthemathematicalmodelandtheperiodofidentificationcriteriaandmethodforoptimizingthesettingsoftheregulator, theoperatorelected a setofexistingones. Developedadaptivecontrolsystemforautomated ID fortemperaturecontrolcontinuouslyactivediffusionplantsugarfactory. Thestudyhighlightedthestagesofsynthesisofadaptivesystemstargetedatstructuringautomatedcontrolsystemusingalgorithmsadaptation. Thesystemcanbeimplementedonthebasisofexistingtypicalmicroprocessorsystembyintroducing a deviceadaptation.